Factors influencing implementation of a self-measured blood pressure program in community health centers: an implementation mapping approach - Serena A. Rodriguez; Serena A. Rodriguez; Serena A. Rodriguez; Fernanda Velasco-Huerta; Mahalia Sampson-Ansah; Ella R. Garza; Ella R. Garza; William B. Perkison; Patenne D. Mathews; Patenne D. Mathews; Catherine Pulicken; Catherine Pulicken; et al. (Frontiers in Public Health)
ObjectivesUncontrolled hypertension is a leading cause of cardiovascular disease, particularly among adults aged 45 years and older. Self-measured blood pressure (SMBP) is an evidence-based intervention that can help patients manage hypertension outside of the clinical setting. We conducted a needs and assets assessment to identify (1) health center adopters and implementers and (2) barriers and facilitators to SMBP adoption and implementation in six community health centers in Texas.MethodsData sources included: (1) needs and assets assessment surveys and semi-structured interviews; (2) site visits with participating health centers; and (3) detailed meeting notes and logs. Leaders and administrators from the participating health centers completed a self-administered 56-item survey. We computed descriptive statistics for survey data. For open-ended survey responses, interview data, and meeting notes, team members labeled the reported and observed barriers and facilitators to program implementation.ResultsBarriers to SMBP adoption and implementation included staffing shortages, limited funding to procure blood pressure devices, and perceived challenges reaching patients and maintaining engagement in an SMBP program. Facilitators included existing hypertension management guidelines, health center familiarity with SMBP programs, and the use of non-physician team members in hypertension management programs. Adopters included leadership professionals and administrators, and implementers included healthcare providers, and non-physician team members.ConclusionFindings inform our understanding of SMBP program adoption, implementation, and importantly, how to best allocate resources to incorporate SMBP programs into clinical workflows.